Compact and low-power wireless headstage for electrocorticography recording of freely moving primates in a home cage - Kaiju, Taro; Inoue, Masato; Hirata, Masayuki; Suzuki, Takafumi (Frontiers in Neuroscience, 2025)
ObjectiveWireless electrocorticography (ECoG) recording from unrestrained nonhuman primates during behavioral tasks is a potent method for investigating higher-order brain functions over extended periods. However, conventional wireless neural recording devices have not been optimized for ECoG recording, and few devices have been tested on freely moving primates engaged in behavioral tasks within their home cages.MethodsWe developed a compact, low-power, 32-channel wireless ECoG headstage specifically designed for neuroscience research. To evaluate its efficacy, we established a behavioral task setup within a home cage environment.ResultsThe developed headstage weighed merely 1.8 g and had compact dimensions of 25 mm × 16 mm × 4 mm. It was efficiently powered by a 100-mAh battery (weighing 3 g), enabling continuous recording for 8.5 h. The device successfully recorded data from an unrestrained monkey performing a center-out joystick task within its home cage.ConclusionThe device demonstrated excellent capability for recording ECoG data from freely moving primates in a home cage environment. This versatile device enhances task design freedom, decrease researchers’ workload, and enhances data collection efficiency.